Statehood as the Issue of the Eurasian Ideology - Yu. V. Sablina (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The purpose of the study: to identify the features of perception of state of the Eurasian ideology.Research methods: combination of civilizational and institutional approaches, chronological, problem-theoretical, historical and comparative, systemic.Results: created the concept of a General perception of state of the Eurasian ideology.Conclusions: Eurasians developed the theory of a perfect state, where power would belong to an elite that knows the divine principles.